DATA-DRIVEN LIFE SCIENCES FROM DATA TO APPLICATIONS - Nur Izzati Mohd. Noh, 1987-, editor 554028; Anthony Nyangson Ste, editor 186968; Zulkifli Abdul Rahman, contributor 445382; Anthony Nyangson Steven, contributor 186968; Fazilah Abd Manan, contributor 294946; Fong Li Yee, contributor 652369; Haryati Jamaludin, contributor 652367; Heeravathy Ramachandran, 1995-, contributor 620488; Jamunaa Ravindran, contributor 652370; Kwek Wei Bin, contributor 652368; Loh Yung Shen, contributor 652366; Nurashikin Ihsan, 1986-, contributor 528183; et al. (Johor Bahru, Johor : PENERBIT UTM PRESS, 2023)
Includes bibliographical references and index.